2016
DOI: 10.1007/s00404-016-4209-4
|View full text |Cite
|
Sign up to set email alerts
|

The SaTH risk-assessment tool for the prediction of emergency cesarean section in women having induction of labor for all indications: a large-cohort based study

Abstract: We have constructed a risk-prediction tool for CS delivery in women with IOL. The risk-assessment tool for the prediction of emergency CS in induced labor has a high negative-predictive value and can provide reassurance to presumed low-risk women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The inclusion criteria that were applied included primigravidae-only women with singleton cephalic presentation deliveries, who were under 40 years old, without the use of epidural analgesia during labour and who self-reported that they were of white-European ethnic background. We selected these inclusion criteria because there is evidence that parity, increased maternal age, use of an epidural and non-white-European ethnic background are all risk factors that have a confounding effect on the outcome of induced labour 3,[18][19][20] . Women who were induced for stillbirths, fetal congenital abnormalities and multiple pregnancies were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The inclusion criteria that were applied included primigravidae-only women with singleton cephalic presentation deliveries, who were under 40 years old, without the use of epidural analgesia during labour and who self-reported that they were of white-European ethnic background. We selected these inclusion criteria because there is evidence that parity, increased maternal age, use of an epidural and non-white-European ethnic background are all risk factors that have a confounding effect on the outcome of induced labour 3,[18][19][20] . Women who were induced for stillbirths, fetal congenital abnormalities and multiple pregnancies were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the large sample size included women who were primigravidae, under 40 years old, whiteEuropean ethnic background, and without epidural use during labour, in order to account for the significant confounding factors of parity, maternal age, ethnicity and labour analgesia on the success of induced labour 3,[18][19][20] .…”
Section: Limitations and Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations were documented in modified risk scoring system based on predesigned and pretested risk factors validated from previous studies. independent risk score was added to give a total score to classify pregnancy in to low risk (<3) intermediate risk (3)(4)(5)(6) and high risk (>6) group.…”
Section: Methodsmentioning
confidence: 99%